Life cycle of Amblyomma calcaratum (Ixodida: Ixodidae) under laboratory conditions - Luz, Hermes R. (2024)
The life-cycle of Amblyomma calcaratum was evaluated experimentally under laboratory conditions using birds (Serinus canaria, Gallus gallus) and rodents (Calomys callosus) as hosts for immatures and a rabbit (Oryctolagus cuniculus) as host for adults. Developmental periods of the non-parasitic stages were observed in an incubator at 27 °C and 90% RH. The passerine S. canaria was the most suitable host for larvae and nymphs whereas the rodent C. callosus was not suitable to both immatures; only one engorged larva was recovered. The suitability of S. canaria for larvae and nymphs of A. calcaratum supports field data regarding passerine birds as main hosts for A. calcaratum immatures. Among the Amblyomma species which life cycle has been evaluated under laboratory conditions, A. calcaratum is one with the longest off-host developmental periods.